The prospect of using greek lignite in an energy portfolio related to power generation - Papanicolaou, C.; Typou, J.; Ioakeim, J.; Kotis, Th.; Foscolos, A. (Bulletin of the Geological Society of Greece, 2013)
The lignite-based power generation contributes 38% towards Greece’s energy independence. Reducing the lignite use while simultaneously importing more expensive natural gas both government deficit and the cost of energy will increase. This surcharge is passed to consumers. Switching to renewable resources invokes an even greater fiscal imbalance, since the costs from the use of wind turbines and solar photovoltaic panels are 87 €/MWh, and 180–284 €/MWh respectively, while natural gas stands at 95 €/MWh and lignite-derived energy is 45 €/MWh. In case of replacing a 300 MW lignite fed power unit with a 300 MW natural gas fed power unit, the loss in income will be 66,540,000 €/year. Coupled with the increased cost of natural gas (31,800,000 €/year) the total is 98,340,000 €/year in addition to the loss of 1235 jobs. Greek authorities intends to replace lignite-fired plants having a total installed capacity of 2531 MW with equivalent natural gas-fired plants resulting in annual total deficit in excess of 787 M€. The targets set by the Greek Ministry of Energy and Climatic Changes to reduce emissions include halving Greek lignite-derived power output from 4800 MW to 2300 MW (>-52%). This move simultaneously increases Greek energy dependence on expensive foreign energy sources and will potentially provoke social unrest at the loss of 12500 jobs with loss of annual income on the order of 670 M€. However, if the existing power output from lignite-fed power plants is maintained, the penalty that PPC (Public Power Corporation) has to pay for the resultant CO2 emissions is significantly smaller (300 M€ at 7.5 €/t of emitted CO2/GWh. Proceeding with the immediate reduction in lignite-fired energy results in economic and social catastrophe (annual income loss:-670 million € + annual CO2 emissions penalty: 348 M€= -322 M€). Lignite-fired plants will become obsolete only when the CO2 emissions penalty exceeds 63.5 €/t of emitted CO2/GWh from a purely economic perspective.